Primary Care Availability, Safety Net Clinics, and Health Insurance Coverage: The Association of These Access Factors With Preventable Hospitalizations. Issue 3 (July 2016) - Murty, Sharanya; Begley, Charles E.; Franzini, Luisa; Swint, J. Michael
Abstract : The objective of the study was to examine the relationship between physician/safety net availability and health insurance coverage and preventable hospitalizations (PHs) in nonelderly adults in an urban area. Preventable conditions (PHs) were identified for nonelderly adults in Harris County using the Texas Health Care Information Collection hospital database. Multivariable logistic regression models examined the association of health insurance and patient proximity to physicians and safety net clinics with the risk of a PH. Safety net availability reduced PH risk by 23% ( P < .05) but only among the uninsured. Lack of health insurance increased PH risk by 30% ( P < .05).